1999
DOI: 10.1161/01.cir.100.14.1494
|View full text |Cite
|
Sign up to set email alerts
|

Expression of NADH/NADPH Oxidase p22 phox in Human Coronary Arteries

Abstract: As atherosclerosis progressed, the expression of p22phox increased through the vessel wall. p22phox might participate in the pathogenesis and pathophysiology of atherosclerotic coronary disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
180
1
5

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 244 publications
(195 citation statements)
references
References 8 publications
9
180
1
5
Order By: Relevance
“…In vivo, macrophage-induced expression of phagocytic gp91phox (Nox2) as well as the catalytic subunit p22phox have been characterized within the lesion of atherosclerotic plaques in human coronary arteries as well as an increase in smooth muscle Nox 4 expression within advanced lesions [140]. Sorescu et al observed the increase in p22phox within the medial layer of the vessel wall as well as the plaque, which agree with earlier studies by Azumi and colleagues [6,140]. The novel observation proved to be that gp91phox expression is found in the plaque and adventitial macrophages, particularly the core of the plaque, where Nox 4 expression is complementary to gp91phox located in the medial smooth muscle layer and luminal surface of the plaque smooth muscle cells.…”
Section: Nadph Oxidase Expression and Function In Vascular Injurysupporting
confidence: 78%
“…In vivo, macrophage-induced expression of phagocytic gp91phox (Nox2) as well as the catalytic subunit p22phox have been characterized within the lesion of atherosclerotic plaques in human coronary arteries as well as an increase in smooth muscle Nox 4 expression within advanced lesions [140]. Sorescu et al observed the increase in p22phox within the medial layer of the vessel wall as well as the plaque, which agree with earlier studies by Azumi and colleagues [6,140]. The novel observation proved to be that gp91phox expression is found in the plaque and adventitial macrophages, particularly the core of the plaque, where Nox 4 expression is complementary to gp91phox located in the medial smooth muscle layer and luminal surface of the plaque smooth muscle cells.…”
Section: Nadph Oxidase Expression and Function In Vascular Injurysupporting
confidence: 78%
“…These findings are in line with recent observations that the expression of NAD(P)H oxidase subunits, such as p22phox, is increased in atherosclerotic coronary arteries. 26,29 Increased O 2 ·Ϫ formation by NAD(P)H oxidase may also contribute to impaired endothelium-dependent vasodilation. Guzik et al 30 demonstrated an inverse relationship between NAD(P)H oxidase activity and endothelium-dependent vasodilation in human saphenous veins obtained from patients with coronary artery disease and identified risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…One of its components, the p22phox is required for oxidase activity. 1 This enzyme complex plays a major role in superoxide ion production in blood vessels. [1][2][3][4] Superoxide ions are known to avidly interact with nitric oxide (NO), reducing its bioactivity by generating peroxynitrite.…”
Section: Introductionmentioning
confidence: 99%
“…1 This enzyme complex plays a major role in superoxide ion production in blood vessels. [1][2][3][4] Superoxide ions are known to avidly interact with nitric oxide (NO), reducing its bioactivity by generating peroxynitrite. [2][3][4] Increased activity of the NAD(P)H oxidase system is expected to be associated with reduced NO levels, vascular dysfunction, hypertension and salt sensitivity.…”
Section: Introductionmentioning
confidence: 99%